Analysis of the Effect of the BI Rate, Inflation and Exchange Rates on the Composite Stock Price Index (Study on the Indonesia Stock Exchange (IDX) for the 2014-2018 period) - Mariska Sisilia; Lidia Rori Hulu; Sani Sutri Cuary; Steven Ginting (Jurnal Mantik, 2020)
The influence of capital market trading is important for the life of the capital market itself. The effect of capital market trading is an important point of consideration by investors. Some of them such as interest rates, inflation and exchange rates are included in the consideration indicators when investing in capital markets. hence the purpose of research to see how much impact of BI Rate (Interest Rate), Inflation and Exchange Rate on CPI in IDX 2014-2018. Where the research uses secondary data, using monthly data listed in monthly Statistic in all bi rate, inflation, exchange rate and monthly JCI data from 2014-2018 with a sample number of 60. Based on the results of bi rate F (Simultaneous) test, inflation and exchange rate simultaneously have a significant influence on the frequency of JCI. from the test result t (Partial) with a partial Variable Only BI Rate that negatively and significantly affects JCI in IDX. This is the case if there is an increase in the variable BI Rate, so that it can make the frequency of the Combined Share Price Index increase. The amount of variation in BI Rate, inflation and exchange rate is only able to explain JCI by 19% , the remaining 81% is explained outside of the research variables.